Acute mesenteric ischaemia with infective endocarditis: is there a role for anticoagulation?. (17th June 2013) - Waqas, Muhammad; Waheed, Shahan; Haider, Zishan; Shariff, Amir Hafeez
Abstract : A case of a 30-year-old woman with an end-stage renal disease and recently diagnosed with infective endocarditis, who presented with acute abdominal pain. An initial assessment of acute appendicitis was made. A CT scan of the abdomen showed a partially occluded superior mesenteric artery with radiographic evidence of ischaemia in an ileal loop. Intraoperatively, a 5–6 cm segment of the distal ileum was found to be non-viable. The segment was resected with the creation of a double-barrel ileostomy. This case report draws attention to the question of a need for anticoagulation for a septic embolus in the superior mesenteric artery. We could not find evidence on the use of postoperative anticoagulation in this scenario. In this case, the patient was started on oral anticoagulation.